Rice Productivity, Zn Biofortification, and Nutrient-Use Efficiency as Influenced by Zn Fertilization Under Conventional Transplanted Rice and the System of Rice Intensification - Choudhary, Anil K.; Sood, Pankaj; Rahi, Shakuntla; Yadav, D. S.; Thakur, O. C.; Siranta, K. R.; Dass, Anchal; Singh, Y. V.; Kumar, Adarsh; Vijayakumar, S.; Bhupenchandra, Ingudam; Dua, V. K.; et al. (Frontiers in Environmental Science, 2022)
North-western Himalayas (NWH) in India have low rice productivity (~2 t ha-1) and quality due to poor crop and nutrient management in predominant Zn-deficient soils. Hence, a field experimentation in NWH compared the conventional transplanted-rice (CTR) and the system of rice intensification (SRI) under three nutrient management practices (NMPs) viz., i) Farmers’ fertilization practice, FYM @ 5 t ha-1 + N:P2O5:K2O @ 50:40:20 kg ha-1 (FFP); ii) Recommended dose of fertilization, FYM @ 10 t ha-1 + N:P2O5:K2O @ 90:40:40 kg ha-1 (RDF); and iii) RDF + Zn-fertilization using ZnSO4 @ 25 kg ha-1 (RDF+Zn). Results revealed that SRI practice harnessed significantly higher rice yield under different NMPs (6.59–8.69 t ha-1) with ~1.3–1.4 and ~3.3–4.3 folds enhancement over the CTR and average rice productivity in NWH, respectively. SRI had greatest improvement in panicle number hill-1 by ~2.4 folds over the CTR. RDF+Zn had significantly higher grain (10.7; 7.9%) and straw yield (28.9; 19.7%) over FFP and RDF, respectively with significant augmentation of Zn-biofortification in grains (11.8%) and Zn-uptake (23.9%) over the RDF. SRI also enhanced the Zn-concentrations in rice grains and straw by ~4.0 and 2.7% over CTR with respective increases of 36.9 and 25.9% in Zn-uptake. Nutrient-harvest-index and partial-factor-productivity of applied nutrients (NPK) had higher magnitude under SRI and RDF+Zn over their respective counterparts i.e. CTR and RDF. In addition, SRI had higher AE-Zn, CRE-Zn and PE-Zn to the tune of 119.6, 63.4 and 34%, respectively over the CTR. Overall, SRI coupled with RDF+Zn in hybrid rice assumes greater significance in enhancing the rice productivity with better Zn-biofortified grains besides higher nutrient-use-efficiencies to combat widespread malnutrition and acute Zn-deficiencies in humans and livestock in north-western Himalayas.